The effect of serum and follicular fluid vitamin D on intracytoplasmic sperm injection outcome - Majeed, Israa; Selman, Mohammad Oda; Qasim, Ban J.; Faisal, Ghasak Ghazi (University of Dicle, 2020)
Vitamin D is a cholesterol derived, fat soluble, steroid substance present in the body. It plays an important role in the female reproductive system and regulating its functions. It is believed that vitamin D improves the endometrial thickness. The relationship between the level of vitamin D and fertilization, embryo quality and Intracytoplasmic sperm injection outcome remains controversial till now. The aim of the study to assess the relation of vitamin D levels in serum and follicular fluid with Intracytoplasmic sperm injection outcome. Eighty-eight women were enrolled in this study. They were classified according to the cause of infertility into case group with female factor and control group with male factor. All women were undergoing Intracytoplasmic sperm injection procedure. Serum and follicular fluid vitamin D levels were measured on the day of oocyte retrieval. It was found that no significant differences in either serum or follicular fluid level of vitamin D between the case and control groups and higher serum and follicular fluid levels of vitamin D are associated with better pregnancy rates after Intracytoplasmic sperm injection. Further studies on vitamin D in male are required to prove its role in the Intracytoplasmic sperm injection. The present study concluded that no significant differences in either serum or follicular fluid level of vitamin D between the case and control groups and higher serum and follicular fluid levels of vitamin D are associated with better pregnancy rates after Intracytoplasmic sperm injection.